Enhanced Endothelin A and B Receptor Expression and Receptor-Mediated Vasoconstriction in Rat Mesenteric arteries after Lipopolysaccharide Challenge - Zhang, Wei; Zhang, Shan-Shan; Huang, Hong-Lang; Song, Bing-Jie; Liu, Xiao; Qi, Zhi (Mediators of Inflammation, 2019)
During organ culture of intact vessels, endothelin receptors (ETRs) were upregulated in vascular smooth muscle cells (VSMCs) by various stimuli, but whether inflammation alters ETR expression in vivo remains unclear. We aimed to explore the effects of lipopolysaccharide (LPS) challenge on ETR expression in the VSMC in vivo. Male Sprague-Dawley rats received a single intraperitoneal injection of LPS (5 mg/kg body weight) or normal saline (NS) for 6 hrs. The function and expression of ETR type A (ETA) and type B (ETB) were evaluated in the mesenteric arteries without endothelium, by using myograph system, real-time quantitative PCR, Western blot, and immunohistochemical staining, respectively. Serum tumor necrosis factor-α (TNF-α) level was assessed by using enzyme-linked immunosorbent assay. The results showed that, compared to control (NS) group, LPS treatment potently enhanced the vasoconstriction mediated by ETA or ETB in rat mesenteric artery, with elevated maximum effects. ETA and ETB expressions in the VSMC were increased at both mRNA and protein levels after LPS treatment, paralleled with activation of the NF-κB pathway and augmented serum TNF-α level. Conclusively, in the rat model of immediate systemic inflammation induced by LPS, ETA and ETB expressions were increased in the mesenteric arterial VSMC, paralleled with enhanced receptor-mediated vasoconstriction and activation of the NF-κB pathway. Our data has for the first time demonstrated the upregulation of ETRs in VSMCs by LPS-induced immediate inflammation in vivo.